2021
DOI: 10.1371/journal.pone.0252420
|View full text |Cite
|
Sign up to set email alerts
|

Current use of attention-deficit hyperactivity disorder (ADHD) medications and clinical characteristics of child and adolescent psychiatric outpatients prescribed multiple ADHD medications in Japan

Abstract: Background/aim Patients with attention-deficit hyperactivity disorder (ADHD) manifest symptoms of hyperactivity, impulsivity, and/or inattention. ADHD medications available in Japan are limited compared with those in Western countries. Prescribing status has not been sufficiently evaluated in clinical settings in Japan. This study investigated the current use of ADHD medications and characteristics of patients who received multiple ADHD medications in a clinical setting in Japan. Methods Study participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…23 Despite concerns about overdiagnosis and inappropriate prescription for ADHD worldwide, many children diagnosed with ADHD may receive insufficient pharmacological treatment in Japan because of caution against the risks compared with the benefits. 24,25 Raman et al indicated that differences in regional clinical guidelines for ADHD treatment recommendations are related to the differences in prescription prevalence across the world. 26 The Japanese guidelines for ADHD are peculiar compared with that of other Asian countries and regions as LDX and GXR can be prescribed while MPH-IR is unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Despite concerns about overdiagnosis and inappropriate prescription for ADHD worldwide, many children diagnosed with ADHD may receive insufficient pharmacological treatment in Japan because of caution against the risks compared with the benefits. 24,25 Raman et al indicated that differences in regional clinical guidelines for ADHD treatment recommendations are related to the differences in prescription prevalence across the world. 26 The Japanese guidelines for ADHD are peculiar compared with that of other Asian countries and regions as LDX and GXR can be prescribed while MPH-IR is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ADHD in school‐aged children varies considerably between countries; for example, white individuals have higher rates of ADHD than Asian individuals 23 . Despite concerns about overdiagnosis and inappropriate prescription for ADHD worldwide, many children diagnosed with ADHD may receive insufficient pharmacological treatment in Japan because of caution against the risks compared with the benefits 24,25 . Raman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Close attention should be paid to environmental factors (e.g., bullying, teacher reprimands, parental abuse) that may influence the symptoms of ADHD. For example, of the 878 patients prescribed the three anti-ADHD medications Methylphenidate, Atomoxetine, and Ganfacine, 43 (4.9%) had used all three medications, indicating that children with severe ADHD symptoms, autistic features and child-parent violence are more likely to experience all three during their treatment have been found to be more likely to experience three medications during treatment (4). Therefore, it is crucial to assess the background of ADHD symptoms and, in doing so, consider interventions for these background factors.…”
Section: Introductionmentioning
confidence: 99%